Rh(I)-Catalyzed Cyclocarbonylation of Allenol Esters to Prepare Acetoxy 4-Alkylidene Cyclopent-3-en-2-ones - Brummond, Kay M. (2009)
[Image: see text] A Rh(I)-catalyzed cyclocarbonylation reaction of allenol esters has been examined and its synthetic viability established for the conversion of trisubstituted allenes to bicyclo-[4.3.0], and -[5.3.0] skeletons possessing an α-acetoxy cyclopentadienone. Tetrasubstituted allenol acetates gave elimination products, providing examples of a cyclocarbonylation reaction between an alkyne and a latent cumulene or cumulene equivalent. Cleavage of the acetate affords a free hydroxyl group illustrating the utility of this method for accessing α-hydroxy carbonyls from allenol esters.